Analysis of Profits and Risks of Ice Tea Franchise Cooperation in Palopo City Perspective Sharia Economics - Nur Amal Mas; Nining, Nining Winda Irawati; Lutfiah Kartika; Muh. Yusran (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This paper discusses how Islamic economic principles influence the expansion of franchise businesses across various sectors. The study analyzes the form of franchise cooperation agreements for Es Teh Nusantara, Es Teh Ori, and Es Teh Poci , as well as a review of Islamic economic principles concerning the benefits and risks of these franchises. The research method used is qualitative, with primary data from observations, in-depth interviews, and documentation. The research findings indicate that the three tea drink franchises exhibit similar cooperation patterns, where the franchisor grants rights to the franchisee and imposes obligations to run the business according to the franchisor's concept. One element of the franchise contract is the licensing by the franchisor to the franchisee to use Intellectual Property Rights (IPR) in exchange for royalty payments. This franchise business falls under syirkah inan , which is a form of capital cooperation between two or more parties with profit or loss sharing according to the capital contributed, using a mudharabah or profit-sharing system. The agreement used is similar to an ijarah agreement, involving the transfer of IPR benefits from the franchisor to the franchisee for a specific period.